Awareness Level of Farm Women About Stress Reducing Improved Farm Tools - Chauhan, Deepali (Indian Journal of Extension Education, 2013)
Two categories of farm women living nearby and far away from Kanpur city, (U.P.)were selected. Further, these two  categories were studied under two sub-categories i.e.resource rich and resource poor farm women. The train tools namely  hand ridger, naveen dibbler, seed treatment drum, PAU seed drill and CIAE seed drill, four row and two row rice  transplanter, fertilizer broad caster, twin wheel hoe, paddy dapoli naveen, wheat dev agro, soy bean dev agro, OUAT paddy thresher ,crri rice winnower, hanging type grain cleaner, standing type ground nut decorticator, octagonal tubular  maize sheller and rotary maize shegller were listed out for assessing awareness level of farm women. Awareness level of  improved farm tools was found to be higher among resource rich farm women of nearby city as compared to resource rich  farm women of faraway from city. Further, resource poor farm women of nearby city were found to be more aware about  from tools as compared to resource poor farm women of faraway from city. Moreover , awareness level was found higher  among resource rich farm women as compared to resource poor farm women. Paddy Dapoli Naveen was used by allfarm  women contrary to hanging type grain cleanerto which all farm women were found unaware.
Keywords: Stress reducing improved farm tools; awareness level; farm women